Shopping tourism amongst Czech customers in the Czech-Polish-German border area of the Euroregion Neisse-Nisa-Nysa - Dědková, Jaroslava; Ungerman, Otakar; Gryszel, Piotr (Quaestiones Geographicae, 2025)
The concept of cross-border shopping tourism covers customer behaviour when purchasing goods in a neighbouring country. The reasons for this behaviour can be varied and most often include a difference in the prices, range or quality of goods. In recent years, cross-border shopping tourism has been affected by the COVID-19 pandemic. Changes in customer behaviour led to the main objective of the paper: to identify cross-border shopping tourism amongst Czech customers before and after the COVID-19 pandemic in the Euroregion Nisa. The research focused on the tri-border area among the Czech Republic, Germany and Poland, which falls within the Euroregion Nisa. The methodology is based on a primary survey of 1028 respondents. The results show significant changes in the frequency and motivation of purchases, with the COVID-19 pandemic playing a key role in the reassessment of customer priorities. It has been found that the main factors influencing shopping tourism in Poland are price differences, whereas in Germany, it is the quality of goods and the difference in the range on offer. In contrast to other European countries, cross-border shopping by Czech customers increased by around 30% after the pandemic. The article provides comprehensive information on the structure of purchases and motives for shopping. The results can be useful for traders in the region but also for policymakers in the border regions. The paper also provides interesting unequivocal results portraying behavioural changes amongst Czech customers.